Arctg(tg(-3п/5))+arcctg(ctg(-3п/5))

Arctg(tg(-3п/5))+arcctg(ctg(-3п/5))
Гость
Ответ(ы) на вопрос:
Гость
[latex]1)\; \; tg(-\frac{3\pi}{5})=tg(-\frac{3\pi}{5}+\pi)=tg\frac{2\pi}{5}\; ,\; \; \frac{2\pi}{5}\in (-\frac{\pi}{2};\frac{\pi}{2})\; \to \\\\arctg(tg(-\frac{3\pi}{5}))=arctg(tg\frac{2\pi}{5})=\frac{2\pi}{5}\\\\2)\; \; ctg(-\frac{3\pi}{5})=ctg\frac{2\pi}{5}\; ,\; \; \frac{2\pi}{5}\in (-\frac{\pi}{2};\frac{\pi}{2})\to \\\\arcctg(ctg(-\frac{3\pi}{5}))=arcctg(ctg\frac{2\pi}{5})=\frac{2\pi}{5}\\\\3)\; \; arcctg(tg(-\frac{3\pi}{5}))+arcctg(ctg(-\frac{3\pi}{5}))=\frac{2\pi}{5}+\frac{2\pi}{5}=\frac{4\pi}{5}[/latex]
Не нашли ответ?
Ответить на вопрос
Похожие вопросы